Main ideas to consider in the elaboration of a new theoretical model of the clinical method. - Luis Alberto Corona Martínez (Medisur)
In this article are exposed the main ideas that has been used for the elaboration of a new theoretical model of the clinical process, with the aim of being used as a teaching content in the Medicine career. Such ideas are: the necessity of a total correspondence between the process method and its objective, the conception of the medical attention process as a decision-taking process, the necessity of highlighting the human dimension of the medical practice, and the convenience of counting with a synthetic representation of the clinical method that facilitates its learning and comprehension. These elements will make possible that the clinical method model facilitates the learning and posterior performance of a more effective and efficient medical attention process, with the following betterment of the medical services’ quality and of the patients’ satisfaction.